Wear Characteristics of FeW/FeW-B4C Coatings Produced by TIG Process - Islak S. (Walter de Gruyter GmbH, 2017)
AbstractIn this study, wear properties of FeW-B4C coatings produced by tungsten inert gas (TIG) process on the AISI 1060 steel were investigated. TIG process was selected because it is a cost-effective approach for melting-based coatings. The treated surfaces were evaluated and characterized by means of scanning electron microscope (SEM), X-ray diffraction analysis, and electron dispersive spectrometry (EDS). The microhardness and wear experiment were also performed by using a microhardness machine and ball-on-disk tribometer. SEM observations showed that the obtained coating had a smooth and uniform surface. According to XRD analysis, borides and carbides phases formed in the coatings. The wear behavior of the coatings was compared with ball-on-disc configuration wear tests, at the same conditions. Average coefficient of friction values of the coatings were obtained at relatively low levels.
Keywords: Mining engineering. Metallurgy; Wear; microstructure; TIG process; TN1-997; TA401-492; coating; Materials of engineering and construction. Mechanics of materials